2006
DOI: 10.1536/ihj.47.237
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis for Operative Mortality in Obstructive Prosthetic Valve Dysfunction Due to Pannus and Thrombus Formation

Abstract: SUMMARYThe objective of the present study was to investigate the risk factors for early hospital mortality in reoperations performed for obstructive prosthetic valve dysfunction. Between January 1994 and April 2005, 63 patients underwent reoperation for obstructive prosthetic valve dysfunction. The mean age of the patients was 40.3 ± 12.8 years. The mitral valve was replaced in 47 (74.6%) patients, the aortic valve in 6 (9.5%) patients, and both valves in 10 (15.9%) patients. Forty-three (68.2%) patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Although surgery is recommended by the recent guidelines (2) for patients in New York Heart Association class III-IV unless surgery is high risk, it has high mortality up to 64% (9). Thrombolysis is an effective therapy for PHVT.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery is recommended by the recent guidelines (2) for patients in New York Heart Association class III-IV unless surgery is high risk, it has high mortality up to 64% (9). Thrombolysis is an effective therapy for PHVT.…”
Section: Discussionmentioning
confidence: 99%
“…Multifactors are involved in its formation. Basically, pannus represent a bioreaction to prosthetic valves associated with coexisting factors such as surgical technique, thrombus organization from inadequate anticoagulation, infection and wall shear stress [3,4]. …”
Section: Commentarymentioning
confidence: 99%
“…In 30 patients with left-sided PVT, Ozkokeli et al reported a surgical mortality of 7.1% in NYHA II-III and 31% in NYHA IV [40]. Surgical mortality reported by Toker et al in 63 cases was 20% [41]. In another series, surgical mortality was 36% in OPVT [9].…”
Section: Surgerymentioning
confidence: 99%
“…In one study in OPVT patients presenting in class IV, mortality of thrombolysis was 13% and that of surgery 33% [9]. A review of the literature showed overall mortality among 89 patients in NYHA class IV to be 7% with thrombolysis [9,52] and ranging from 17 to 54% in operated patients [1][2][3][4]32,41], whereas in NYHA class I-III patients, mortality was no more than 5% with both treatment modalities [9,36,46,57,61,70].…”
Section: Comparison Of Treatment Strategiesmentioning
confidence: 99%